Strategi Penyandang Disabilitas dalam Mengakses Pangan dengan Keterbatasan Finansial di Kota Ambon - Sopacua, Maria M (Master of Epidemiology, Faculty of Public Health, Diponegoro University, Indonesia, 2025)
Background: In Ambon, improving the quality of life of people with physical disabilities is still largely ignored by the local government and beyond. The gap is widening because they are stigmatized as “helpless”. This causes them to experience social discrimination and to be “othered”. As a result, it is difficult to meet their financial needs and this affects how they access food.Methods: This research uses a qualitative method conducted on the people of Ambon City from February - April 2021. Data collection techniques used observation and in-depth interviews.Results: I interviewed seven male participants based on their experiences to look at the relationship between “disabled bodies” and food miles and how the two can be intertwined. Physical geographical constraints and unfriendly constructions for people with disabilities are barriers for them to reach food destinations. On the other hand, income insecurity also makes it more difficult for them to obtain good and safe food. However, this does not mean that they have no power. To reduce the inequality of food access, they do gardening or borrow money from relatives.Conclusion: The results of this study can inform that the local government's concern is not enough to help people with physical disabilities in accessing food, but also requires support from the environment and the community.